Management of pregnant laboring women during COVID-19 pandemic - Kajal Jain; Nidhi Bhatia; Anju Grewal; Sunil T Pandya; Sunanda Gupta; Rashmi Bagga; Anjan Trikha (Wolters Kluwer Medknow Publications, 2020)
Since its first outbreak in December 2019 in Wuhan, China, coronavirus disease 2019 (COVID-19) has become a global public health threat. In the midst of this rapidly evolving pandemic condition, the unique needs of pregnant women should be kept in mind while making treatment policies and preparing response plans. Management of COVID-19 parturients requires a multidisciplinary approach consisting of a team of anesthesiologists, obstetricians, neonatologists, nursing staff, critical care experts, infectious disease, and infection control experts. Labor rooms as well as operating rooms should be in a separate wing isolated from the main wing of the hospital. In the operating room, dedicated equipment and drugs for both neuraxial labor analgesia and cesarean delivery, as well as personal protective equipment, should be readily available. The entire staff must be specifically trained in the procedures of donning, doffing, and in the standard latest guidelines for disposal of biomedical waste of such areas. All protocols for the management of both COVID-19 suspects as well as confirmed patients should be in place. Further, simulation-based rehearsal of the procedures commonly carried out in the labor room and the operation theaters should be ensured.